Assessment as information practice : evaluating collections and services - Haddow, Gaby, 1958-; White, Hollie, 1980- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Assessment as Information Practice provides information about a range of collection and service-based assessment approaches that can be applied in different contexts to benefit institutions and the users they serve by enhancing quality, efficiency and effectiveness. With contributions from practitioners and researchers in Australia, New Zealand, Thailand and the United States, the chapters discuss practical and theoretical aspects of assessment in collecting institutions. Each chapter focuses on specific assessment approaches or contexts, while providing guidance on method and use. The chapters can be read alone, or as a series to gain an appreciation of assessment approaches, including: assessment-oriented research; storytelling; design thinking; data visualisation; mixed methods assessment for digital resources; data for institutional repository assessment; bibliometric methods; and impact assessment. Assessment as Information Practice serves as a resource for practitioners involved in assessment activities. Detailing the processes and considerations that will contribute to more effective and sustainable assessment programs, the book is also relevant to faculty, researchers and students working in the information sector"--
Assessment as Information Practice / Gaby Haddow -- Research Design and the Relationship Between Assessment and Research / Starr Hoffman -- Storytelling for the Evaluation of GLAM Programmes and Services / Anne Goulding -- Facilitating Iteration in Service Design in Libraries / Songphan Choemprayong -- The Assessment and Analysis of Materials Availability: A Mixed Methods Approach / David Wells -- Data Visualisations for Library Collections: Applying an Inquiry-based Approach / Susan Payne, David Dudek, Bonnie Wittstadt, Mark Cyzyk and Tom Edward -- Moving beyond Downloads and Views when Assessing Institutional Repositories / Hollie White -- Taking a Quantitative Approach: Bibliometric Methods in Academic Libraries / Gaby Haddow -- Assessment in Practice: Effectiveness and Impact / Gaby Haddow and Hollie White.
OCLC-licensed vendor bibliographic record.
Keywords: Collection development (Libraries) -- Evaluation; Public services (Libraries) -- Evaluation; Collection development (Libraries) -- Evaluation -- Case studies; Public services (Libraries) -- Evaluation -- Case studies